99mTc TRAINING COMPLEX WITH LIGAND AND ALKALI CATION TETRAFOSFORADOS ACYCLIC AND MACROCYCLIC - Vidal, M. (1998)
The tetraphosphorus ligands, potential complexing agents for radioactive nucleides and alkali metals cations, constitute the essential objective of this work. The study of their complexing ability of these tetraphosphorus ligands are described.